Pseudomyxoma Peritonei: A Case Report of a 73-Year-Old Male Presenting with Abdominal Distension - Pereira, Ricardo; Côrte-Real, Mónica; Casimiro, Hugo Jorge; Carreira, Joana; Morgado, Francisco; Gonçalves Pereira, Rita (International Journal of Innovative Research in Medical Science, 2024)
Pseudomyxoma peritonei is characterized by diffuse mucinous ascites and mucinous implants on the peritoneal surfaces. The authors report a case of a 73-year-old man with complaints of abdominal distention, nausea, fatigue, and asthenia for the past two months. The patient underwent diagnostic laparoscopy, and histological examination revealed pseudomyxoma peritonei secondary to low-grade mucinous carcinoma with intestinal differentiation. The patient was referred to Oncology for hyperthermic intraperitoneal chemotherapy along with complete cytoreduction surgery.